2016
DOI: 10.1016/j.jtrangeo.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The replication and reduction of automobility: Findings from Aotearoa New Zealand

Abstract: ABSTRACT:In this paper, we examine the factors that contribute to the replication or reduction of automobility amongst young adults. Semi-structured interviews conducted in Aotearoa New Zealand, with 51 drivers and non-drivers, aged 18-35 years old, form the empirical material. The findings build upon previous research and extend understandings of how seven explanatory factors; perceptual, value and preference, social, built environment, economic, legal/ policy and technological, work both to continue the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…This paper, focuses on mobility practices which differ from the auto-centric norm, but also includes participants who selfidentified as drivers. Trends reproducing automobility were evident in this research, and have been published elsewhere (Hopkins & Stephenson, 2016).…”
Section: Research Approachsupporting
confidence: 73%
See 2 more Smart Citations
“…This paper, focuses on mobility practices which differ from the auto-centric norm, but also includes participants who selfidentified as drivers. Trends reproducing automobility were evident in this research, and have been published elsewhere (Hopkins & Stephenson, 2016).…”
Section: Research Approachsupporting
confidence: 73%
“…In 9 of 14 countries analysed by Delbosc & Currie (2013), licensing rates were in decline, while 5 countries (Finland, Israel, The Netherlands, Switzerland and Spain) reported business-as-usual increases to generation Y's licensing trends. In New Zealand, there has been a decline in the percentage of 15-34 year olds with a full driver's licence between 1990 and 2014 1 (NZ Ministry of Transport, 2014;Hopkins & Stephenson, 2016). Average national vehicle kilometres travelled (VKT) has been static for the 15-24 and 25-34 age groups (NZ Ministry of Transport, 2014;Hopkins & Stephenson, 2016), but these data are likely to disguise wide regional variability.…”
Section: Generation Y Mobilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It "took cues from multiple theories and explanations of behaviour, and aimed to bridge the divide between research traditions centred on the individual and those focused on wider social and technological influences" (Stephenson et al, 2015a: page 117). Since its first publication it has been used to support enquiry into a variety of topics, including timber companies use of drying technologies (Bell et al, 2014), the impact of different home energy advice approaches (Scott et al, 2016), mobility and the future of transport (Stephenson et al, 2015b;Hopkins and Stephenson, 2014;Hopkins and Stephenson, 2016), individuals' actions on greenhouse gas emissions (Young and Middlemiss, 2012), and energy behaviour in higher education in Malaysia (Ishak et al, 2012).…”
Section: An Energy Cultures Approachmentioning
confidence: 99%
“…However, working young adults might be more car dependent because employment often implies the demand to have a driving license (as it is assumed to be associated with adulthood and responsibility) and because of greater financial means and the possibility to own/receive a car [22, 23]. One US study showed that the vast majority (90.4%) of working young adults commute by car [24].…”
Section: Introductionmentioning
confidence: 99%